Optimalisasi layanan teknologi digital berbasis Total Quality Management (TQM) di Dinas Kearsipan Dan Perpustakaan Provinsi Jawa Tengah - Safira, Nur Aeni; Ahwan, Muh Ahlis (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2024)
Purpose. This study aims to assess the optimization of iJateng services at the Dinas Kearsipan dan Perpustakaan Provinsi Jawa Tengah using Total Quality Management (TQM) principles. Additionally, it seeks to identify challenges and propose strategies for enhancing service performance and efficiency. Methodology. Employing a qualitative descriptive approach, this research collects data through observation, interviews, and documentation to provide an in-depth analysis of the optimization process. Results and discussion. Findings reveal that the optimization of iJateng services incorporates TQM elements, including 1) benchmarking, 2) continuous improvement, 3) staff empowerment, 4) teamwork, 5) user identification, 6) listening to users, 7) process analysis, and 8) statistical process control. Despite these efforts, challenges persist, such as a limited reading culture, budget constraints, and insufficient socialization efforts. Conclusions. The optimization of digital library services through the iJateng application has been implemented effectively using TQM principles, demonstrating a commitment to continuous improvement. Libraries aiming to develop or enhance digital services can adopt TQM strategies to enhance service quality and user satisfaction. Addressing the identified obstacles, particularly in fostering a reading culture and improving outreach, will further enhance the impact and accessibility of digital library services.